HUBUNGAN ASUPAN GIZI DENGAN AKTIVITAS BELAJAR SISWA SEKOLAH DASAR - Dwi Rahayu Ningsih (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2018)
The purpose of this research is to know (1) nutrientintake, (2) learning activities, and (3) nutritional intakerelationship with learning activity Taman Muda (SD)Tamansiswa Sekota Yogyakarta. The research population isstudents and students in Taman Muda (SD) TamansiswaSekota Yogyakarta with 94 students. This study includedsample research. Random sampling technique, ie sampletaken 60% plus 10% for missing data. Thus, the sample ofthis study was 57 + 6 = 63. This study included the type ofex-post facto research. The data tested the validity, reliabilityand data analysis techniques Product Moment correlation.The results showed that there is a positive and significantrelationship between the variables between nutritionalintake with learning activities. The determinant coefficient(R2) is 0.310, meaning that the contribution contributionof nutritional variable to learning activity variable is31%, while the rest 69% is influenced by other factors notdiscussed in this research.